Target functions of the conceptual model for adaptive monitoring of integrated security in material processing systems. (2021) - Parashchuk, Igor; Kotenko, Igor
Abstract: The paper explores an approach aimed to formulate particular and generalized target functions for a formal specification of the problem of adaptive and optimal monitoring of integrated security in modern material processing systems and technologies. The formulation of the target functions is carried out taking into account the whole variety of factors affecting the procedures of observation, assessment and prediction within the conceptual model of adaptive monitoring. The stages of implementation of these target functions as a joint sequential dynamic adaptation of the parameters of observation, assessment and prediction procedures (i.e. monitoring parameters) of the integrated security state are proposed. Practical implementation of the proposed approach to the formalization of monitoring tasks will increase its effectiveness by improving the nonredundancy, reliability and accuracy of the state assessment and prediction of integrated security for material processing systems and technologies.